India’s Janani Suraksha Yojana: Challenges Ahead - Jennings, Timothy; Singh, Vikram; Rodriguez, Frances M; Patel, Isha (Journal of Pharmacy Practice and Community Medicine)
In August of 2016, an article was published in The Hindu detailing a terrible story. The article, written by Vidya Krishnan and entitled “Labour pain: Sitapur’s maternity racket,” tells of a young India couple in the state of Uttar Pradesh who were gouged for money while trying to participate in a free government program to promote births by trained professionals called the Janani Suraksha Yojana, or JSY. This program was designed to help families stay safe during the process of childbirth in compliance with the World Health Organization’s goals.[1] The extortion came in the form of demanded tips from the people involved and threats were made when the victims did not initially comply. The program offers enough money to the participants to pay for the birth with some leftover, but, due to a loophole in the system, this young couple had yet to receive anything.